Tris(pentafluorophenyl)borane-Catalyzed Stereoselective C-Glycosylation of Glycals: A Facile Synthesis of Allyl and Alkynyl Glycosides - Gaurav, Anand; Azeem, Zanjila; Mandal, Pintu Kumar (Synthesis, 2023)
In modern advances, tris(pentafluorophenyl)borane (commonly known as BCF) catalyst has risen to prominence owing to its extensive versatility in the use of myriad of organic reactions. An efficient and highly stereoselective α-C-glycosylation strategy is presented by employing a catalytic amount of B(C6F5)3 under mild reaction conditions en route to 2,3-unsaturated C-glycosides. The reaction features a broad functional group tolerance including a variety of glycals coupled with allyltrimethylsilane and trimethylsilylphenylacetylene to access the corresponding 2,3-unsaturated allyl- and alkynyl-C-glycosides with excellent α-selectivity. The reaction proceeds in good to excellent yields via concomitant borane activation of glycal donor under mild conditions.
Keywords: carbohydrate; glycal; tris(penta; fluorophenyl)borane; stereoselective; C-glycosylation; 2,3-unsaturated C-glycosides